2010
DOI: 10.1111/j.1365-2362.2010.02424.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral glucose loading attenuates endothelial function in normal individual

Abstract: Our study showed that oral glucose loading attenuates FMD and shortens elapsed time at the maximum after-hyperaemia diameter, and the effect of glucose fluctuation on atherosclerosis in individuals with normal glucose tolerance remains despite only the attenuation of endothelial function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 45 publications
(91 reference statements)
3
23
0
Order By: Relevance
“…The subjects of the OG and control groups had previously been included in our study of postprandial attenuation of FMD [12]. The test meal for the TM group (Table2) was a commercial energy-supplement food (CalorieMate®, Otsuka Pharmaceutical Co., Ltd., Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The subjects of the OG and control groups had previously been included in our study of postprandial attenuation of FMD [12]. The test meal for the TM group (Table2) was a commercial energy-supplement food (CalorieMate®, Otsuka Pharmaceutical Co., Ltd., Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Attenuation of brachial artery FMD is induced by postprandial hyperglycemia in subjects with normal glucose tolerance and in prediabetic or diabetic patients, and FMD is negatively correlated with plasma glucose (PG) levels after oral glucose loading [8-11]. We have previously reported that postprandial hyperinsulinemia also induces attenuation of FMD in persons with normal glucose tolerance [12]. Several studies have evaluated differences in FMD attenuation after meals with different carbohydrate contents [13-17].…”
Section: Introductionmentioning
confidence: 99%
“…Similar observations regarding increased endothelial activation markers were also made following OGTT (42,43) . Recently, Watanabe et al (44) and many others observed that an OGTT significantly decreased endothelial function assessed by ultrasonography that was correlated with postprandial hyperglycaemia (r 20·61; P,0·05) and insulin release (r 2 0·55; P, 0·05). Importantly, some groups have observed no demonstrable increases in postprandial oxidative stress (malondialdehyde (MDA), nitrate/ nitrite and H 2 O 2 levels) or decreases in plasma antioxidant capacity (i.e.…”
Section: Pathophysiology Of Oxidative Stressmentioning
confidence: 99%
“…However, Major-Pedersen et al (2008) reported that oral glucose load does not cause endothelial dysfunction in healthy individuals when the mean glucose level is at 5.6 mmol/L and insulin is at 27.2 mmol/L, at 2 hours after glucose [11]. Nevertheless, a recent study has shown that oral glucose load attenuated flow-mediated dilation in brachial artery of healthy individuals [12]. …”
Section: Introductionmentioning
confidence: 99%